Winter weather and lake‐watershed physical configuration drive phosphorus, iron, and manganese dynamics in water and sediment of ice‐covered lakes. (22nd March 2017) - Joung, DongJoo; Leduc, Meagan; Ramcharitar, Benjamin; Xu, Yaoyang; Isles, Peter D. F.; Stockwell, Jason D.; Druschel, Gregory K.; Manley, Tom; Schroth, Andrew W.
Abstract: While decreasing occurrence and duration of lake ice cover is well‐documented, biogeochemical dynamics in frozen lakes remain poorly understood. Here, we interpret winter physical and biogeochemical time series from eutrophic Missisquoi Bay (MB) and hyper‐eutrophic Shelburne Pond (SP) to describe variable drivers of under ice biogeochemistry in systems of fundamentally different lake‐watershed physical configurations (lake area, lake : watershed area). The continuous cold of the 2015 winter drove the MB sediment‐water interface to the most severe and persistent suboxic state ever documented at this site, promoting the depletion of redox‐sensitive phases in sediments, and an expanding zone of bottom water enriched in reactive species of Mn, Fe, and P. In this context, lake sediment and water column inventories of reactive chemical species were sensitive to the severity and persistence of subfreezing temperatures. During thaws, event provenance and severity impact lake thermal structure and mixing, water column enrichment in P and Fe, and thaw capability to suppress redox front position and internal chemical loading. Nearly identical winter weather manifest differently in nearby SP, where the small surface and watershed areas promoted a warmer, less stratified water column and active phytoplankton populations, impacting biogeochemical dynamics. In SP, Fe and P behavior under ice were decoupled due to active biological cycling, and thaw impacts were different in distribution and composition due to SP's physical structure and related antecedent conditions. We find that under ice biogeochemistry is highly dynamic in both time and space and sensitive to a variety of drivers impacted by climate change.